Grid-based coordinated control of mobile robot formations : : doctoral thesis - Miklić, Damjan 1980 (D. Miklić ; Fakultet elektrotehnike i računarstva, 2013)
ABSTRACT: This dissertation presents a controller design framework and algorithms for controlling formations of autonomous vehicles. It addresses all three fundamental issues of formation control, namely establishing formations, navigating in formation through an obstacle-ridden environment, and switching between different formations. These issues are treated both in a centralized and a decentralized way. To deal with the complexity of multi-vehicle control, we propose a formation abstraction by the means of a virtual rectangular grid. This grid-based approach enables the decoupling of group motion and formation configuration. The grid acts as a virtual leader, keeping the formation together and providing tracking references for the vehicles. Formations are represented in discrete space, as grid cell occupations. Transitions between different formations are modeled using a matrix-based framework that is well-established in the manufacturing systems domain, yet it has not been applied to multi-vehicle coordination problems before. We use it to design provably correct and safe transition sequences between arbitrary formations. Combined with algorithms for selecting appropriate evasion formations, the transition scheduling algorithm enables safe formation navigation in obstacle-ridden environments. The discrete event scheduling strategy operates with the assumption that vehicles can transition between two neighboring grid cells without entering any of the other cells. We provide a controller tuning procedure which insures that the vehicle-level motion controllers can satisfy such performance guarantees. We also develop a hybrid controller architecture which integrates group motion control, discrete-event formation transition scheduling and vehicle-level motion controllers into a coherent formation control framework. Simulated and experimental results confirm the capability of our architecture to deal with all aspects of formation control, from assembling formations to safe navigation through environments with obstacles. -